Herbal Medicine Between Current Practice and Knowledge Needs: A National Cross-Sectional Survey in Iraq - Humadi, Suhad; Hassan, Saif M.; Ahjel , Salam W. (Iraqi Journal of Pharmaceutical Sciences, 2024)
Herbal medicine, a complementary and alternative medicine component (CAM), has become popular worldwide, and the population has dramatically increased its utilization. Its widespread use within the general community makes it crucial to recognize how pharmacists can satisfy customers’ information needs and lead to the quality use of complementary medicines within the pharmacy setting. Thus, this study was planned to evaluate knowledge, practice, and attitude toward herbal products among community pharmacists practicing in Bagdad and several other Governments in Iraq to evaluate the current pharmacist’s role in patient counseling on the one hand; and predicting factors preventing pharmacists from occupying their full scope of practice on the other hand.